1973
DOI: 10.1021/j100641a006
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance study on the acrylic acid anion radical and its protonation in some irradiated frozen solutions

Abstract: An esr study has been carried out for reactions of electrons with acrylic acid (AA) in a variety of irradiated frozen solutions. The electron adducts of acrylic acid [CEL-CH-COOH]" were found to be formed in some matrices, such as 2-methyltetrahydrofuran (MTHF), triethylamine (TEA), and 3-methylhexane (MHX). The hyperfine couplings to the end CH2 protons (oq 13 G) are consistent with the INDO MO calculation made for the delocalized anion w radical. The post-irradiation thermal annealing of the frozen MTHF-AA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…4 b. A superposition of the seven-line MTHF radical and a triplet assigned to the TPGDA radical anion is observed. The hyperfine coupling constants derived [7] for the TPGDA radical anion (see Tab. 2) are similar to those given by Iwasaki [16] for the anion of acrylic acid. From the triplet structure of the EPR spectrum, resulting from isotropic coupling of two protons, it is concluded that the TPGDA radical anion is a p-radical exhibiting the resonance structures (8).…”
Section: Anionic Pathway Of Radical Formation -Epr Results and Discussupporting
confidence: 86%
“…4 b. A superposition of the seven-line MTHF radical and a triplet assigned to the TPGDA radical anion is observed. The hyperfine coupling constants derived [7] for the TPGDA radical anion (see Tab. 2) are similar to those given by Iwasaki [16] for the anion of acrylic acid. From the triplet structure of the EPR spectrum, resulting from isotropic coupling of two protons, it is concluded that the TPGDA radical anion is a p-radical exhibiting the resonance structures (8).…”
Section: Anionic Pathway Of Radical Formation -Epr Results and Discussupporting
confidence: 86%
“…Reaction 9 was observed in this work only with cinnamic acid. The rate of reaction 10 OH-r2ccrco2h-->-R2CHCRC02- (10) or buffer with all the other monoprotonated radicals is very high. Hence equilibrium 9 cannot be achieved.…”
Section: Discussionmentioning
confidence: 97%
“…2 Irradiation and ESR measurements were carried out in a manner similar to those described in our previous paper. 1 The signals of Mn2+ and DPPH were used as a marker for the magnetic field as well as for the spectral intensity standard. Irradiation by uv light was made with a high-pressure mercury lamp (Ushio 500W) at 77 K. The line shape analyses and the INDO MO calculations were made using a Facom 270-30 computer.…”
Section: Methodsmentioning
confidence: 99%